FIKIH ZAKAT SIMPANAN DI BANK DAN HUKUM-HUKUMNYA - Waluya, Atep Hendang (Universitas Negeri Surabaya, 2017)
The potential of zakah of savings on Banks in Indonesia in 2011 reached 17 T. According to the jumhur (konsensus) of contemporary fuqaha (jurist), saving in banks, essentially, are accounts receivable (qardh). There is a difference of opinion among the fuqaha about the zakah on accounts receivable. However, a strong opinion is that saving in banks is accounts receivable to mali badzil (people who can afford to pay debts and not delay payments) therefore deposits in banks both conventional and sharia are obliged to be paid the zakah when they reach nishab and haul. The nishab is the same as gold or silver. The size is 2,5%. If follow the gold nishab, then saving about Rp. 45.132.620,00 then must pay zakah about Rp. 1.128.315,00. If follow silver nishab, then the savings in the bank about Rp. 6.515.250,00 are required to pay zakah about Rp. 162.881,25. It is possible to combine banknotes, gold, silver and merchandise (‘urudh tijarah) in determining nishab deposits in banks. If there any profits on saving that invested (deposits) then the saving and profits must be paid the zakah, if the investment is on the halal and not contrary to syara. There is no zakah on the profits from saving invested (deposits) on the forbidden enterprises or from the interest of savings in a conventional bank